Responsiveness Mediates Accountability and Transparency for Stakeholder Participation in Pondok Pesantren: Responsiveness,Accountability, Transparency, Participation, Pondok Pesantren - Munir Is’adi; Abdur Rakhman Wijaya (JURNAL ECONOMINA, 2026)
This study investigates how perceived accountability (PA) and perceived transparency (PT) shape stakeholder participation (PP) in Pondok Pesantren, with perceived responsiveness (PR) as a mediator. Using a quantitative, causal design and Partial Least Squares-Structural Equation Modelling (PLS-SEM), data were collected from 89 stakeholders (students, parents/ guardians, alumni, local community, and donors) across several Pesantren in Jember. The measurement model shows strong reliability and validity (CR = 0.922—0.964; AVE > 0.50; all loadings > 0.70; VIF < 5). The structural model explains 81.5% of the variance in participation (R-square = 81.5%) and 77.3% in responsiveness (R-square = 0.773), with high predictive relevance (Q-Square PP = 0.595; Q-Square PR = 0.558). Key paths indicate that PR → PP is the strongest predictor (O = 0.539; p < 0.001), PT → PR (O = 0.331; p = 0.0012) are significant. Mediation tests confirm full mediation of PR in the PA → PR (O = 0.313; p = 0.002) and partial mediation in the PT → PP link (O = 0.178; p = 0.026). The findings suggest that accountability and transparency foster participation when they are experienced as responsiveness, offering a governance pathway aligned with amanah, ihsan, and shura..